Insights into the mechanisms underlying efficient Rhizodegradation of PAHs in biochar-amended soil: From microbial communities to soil metabolomics. (November 2020) - Li, Xiaona; Song, Yang; Bian, Yongrong; Gu, Chenggang; Yang, Xinglun; Wang, Fang; Jiang, Xin
Graphical abstract: Highlights: Combining biochar and plant roots promoted cooperation of PAH degraders. Lipid, amino acid and carbohydrate metabolism linked to PAH degradation. There were strong cooccurrences between microbial community members and metabolites. Biochar modulated fatty acid metabolism, promoting large-molecular PAH degradation. Combining biochar and plant roots upregulated overall metabolism in PAH degradation. Abstract: The combined effects of biochar amendment and the rhizosphere on the soil metabolic microbiome during the remediation of polycyclic aromatic hydrocarbon (PAH)-contaminated soil remain unknown. In this study, we attempted to characterize a PAH degradation network by coupling the direct PAH degradation with soil carbon cycling. From microbial community structure and functions to metabolic pathways, we revealed the modulation strategies by which biochar and the rhizosphere benefited PAH degradation in soil. Firstly, some PAH degraders were enriched by biochar and the rhizosphere, and their combination promoted the cooperation among these PAH degraders. Simultaneously, under the combined effects of biochar and the rhizosphere, the functional genes participating in upstream PAH degradation were greatly upregulated. Secondly, there were strong co-occurrences between soil microbial community members and metabolites, in particular, some PAH degraders and the metabolites, such as PAH degradation products or common carbon resources, were highlighted in the networks. It shows that the overall downstream carbon metabolism of PAH degradation was also greatly upregulated by the combined effects of biochar and plant roots, showing good survival of the soil microbiome and contributing to PAH biodegradation. Taken together, both soil carbon metabolism and direct contaminant biodegradation are likely to be modulated by the combined effects of biochar and plant roots, jointly benefitting to PAH degradation by soil microbiome. Our study is the first to link PAH degradation with native carbon metabolism by coupling sequencing and soil metabolomics technology, providing new insights into a systematic understanding of PAH degradation by indigenous soil microbiome and their networks.